DIGITAL STORYTELLING IN EFL CLASSROOM: SPEAKING AND CREATIVE THINKING SKILLS - Dinda Hanifa Dewi; Arjulayana Arjulayana; Yudhie Indra Gunawan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigated EFL students’ speaking and creative thinking skills through digital storytelling activities using Book Creator. The objectives were to assess changes in speaking performance, evaluate creative thinking levels, and explore the Book Creator’s role in supporting both skills. This study employed a pre-experimental one-group pretest–posttest design within a quantitative framework. Data were collected through pretest and posttest speaking scores, rubric-based creative thinking assessment, and field notes. The findings showed a marginal increase in mean speaking scores from 78.30 to 78.48. However, the paired-sample t-test indicated that the improvement was not statistically significant (Sig. = 0.831). In contrast, students demonstrated competence to excellent creative thinking, evident in their ability to generate and express ideas through visual, written, and audio elements. Field notes indicated increased comfort in independent recording, although speaking anxiety persisted. These findings suggest that digital storytelling facilitated idea expression and organization but did not significantly improve speaking performance. This study contributes by integrating multimodal digital storytelling into EFL contexts, highlighting its potential for fostering creativity despite its limited impact on speaking performance. Future research may further explore cognitive load, interactive speaking practices, and other 4C skills to provide a more holistic understanding of DST in EFL contexts.